PERAN SUTRADARA DAN EDITOR VIDEO DALAM FILM FIKSI IMPIAN TERTULIS - Ridho Artha Arvizu, (2024)
The Fiction Film "Impian Tertulis" discusses the life of a disabled person who dreams of becoming a writer. This film contains many elements of literacy and motivation in achieving your dreams. The aim of this film is to increase understanding of the importance of respecting fellow humans and that every human being has the same opportunity to achieve their dreams. This film reveals that in life, humans have equality regardless of shortcomings. And the Editor plays an important role in the post-production process of this film by injecting and visualizing the concept. This fictional film briefly and clearly conveys a message about the importance of a strong sense of desire in achieving dreams, even though there are many shortcomings and problems in the process.